Human Monkeypox: The Emerging and Deadly Infectious Disease - Syed Zulfiquar Ali Shah, Abdul Ghani Rahimoon, Imran Karim, Ghulam Fatima Dayo, Ramsha Khan, Syed Jahanghir, (Pakistan Journal of Medical & Health Sciences, 2023)
The monkeypox (Mpox) virus is a closely related orthopoxvirus to the virus called variola responsible for smallpox. In 1958, the first case of monkeypox emerged among captive primates used for research, so it was dubbed monkeypox. 1971 marked the first human victim of monkeypox in the Congo Republic.1Like variola (VARV), cowpox (CPX) and vaccinia (VACV), MPXV is a member of the family of DNA that is double-stranded viruses known as the genus Orthopoxvirus2. There are two ways that MPXV enter the cell of the host: either by endosomal uptake via a macropinocytosis mechanism involving actin, or by combining among the ligands on the envelope of the virus and the receptors of host cell on the membrane following the components of envelope of virus swiftly spread in the membrane3. The virus then replicates its genetic material in the cell nucleus and secretes viral protein and enzymatic components into the cytoplasm, where they weaken the cell's defenses and promote the development of early genes4.